Multitube monitors: a new-generation of neutron beam monitors. (1st May 2022) - Lafont, F.; Barkats, D.; Buffet, J.-C.; Cuccaro, S.; Guerard, B.; Lai, C.-C.; Marchal, J.; Pentenero, J.; Sartor, N.; Hall-Wilton, R.; Kanaki, K.; Robinson, L.; et al.
Abstract: With the renewal of many neutron science instruments and the commissioning of new neutron facilities, there is a rising demand for improved neutron beam monitoring systems with reduced beam perturbations and higher counting rate capability. Fission chambers are the most popular beam monitors; however, their use on some instruments may be prevented by the background generated by fast neutrons emitted during neutron captures in 235 U and by neutrons scattered in the material of the fission chamber. Multitube detectors, on the other hand, offer a good alternative with minimum beam perturbations. The purpose of this paper is to report and analyse the results of the measurements performed with several Multitubes used for beam monitoring. We show that the transparency of Multitube beam monitors is 97.6 ± 0.4 %, and that their detection efficiency is uniform, with a deviation from the mean value <0.7 %. A counting rate reduction of 10 % due to pile-up effects is measured at a rate of 550 kHz. In addition to neutron beam intensity monitoring, the Multitube can be configured for 1-dimensional or 2-dimensional localisation. We present the preliminary results of these additional functionalities.